Paesaggi mentali e vivibilità nei luoghi alpini. Trasformazione dei luoghi in paesaggi. Percezione, sense-making e turismo - Morelli, Ugo (Ri-Vista. Research for landscape architecture, 2015)
In the transformation process by which the sites become landscapes and also take the form of tourist landscapes, historical-evolutionary, affective, cognitive and socio-economic aspects are involved; their complexity requires a selection of perspective to be analyzed. This is a process both of introjection and projection, that, at the same time, produces knowledge, by means of symbolic competence. It is giving them a sense, then, that we know the places and the nature to which we belong. This essay examines the implications of the question through an approach that favours the orientations of applied cognitive sciences.